Death-ision: the link between cellular resilience and cancer resistance to treatments - Gustavo Baldassarre; Ivana L. de la Serna; François M. Vallette (Molecular Cancer)
Abstract One of the key challenges in defeating advanced tumors is the ability of cancer cells to evade the selective pressure imposed by chemotherapy, targeted therapies, immunotherapy and cellular therapies. Both genetic and epigenetic alterations contribute to the development of resistance, allowing cancer cells to survive initially effective treatments. In this narration, we explore how genetic and epigenetic regulatory mechanisms influence the state of tumor cells and their responsiveness to different therapeutic strategies. We further propose that an altered balance between cell growth and cell death is a fundamental driver of drug resistance. Cell death programs exist in various forms, shaped by cell type, triggering factors, and microenvironmental conditions. These processes are governed by temporal and spatial constraints and appear to be more heterogeneous than previously understood. To capture the intricate interplay between death-inducing signals and survival mechanisms, we introduce the concept of Death-ision. This framework highlights the dynamic nature of cell death regulation, determining whether specific cancer cell clones evade or succumb to therapy. Building on this understanding offers promising strategies to counteract resistant clones and enhance therapeutic efficacy. For instance, combining DNMT inhibitors with immune checkpoint blockade may counteract YAP1-driven resistance or the use of transcriptional CDK inhibitors could prevent or overcome chemotherapy resistance. Death-ision aims to provide a deeper understanding of the diversity and evolution of cell death programs, not only at diagnosis but also throughout disease progression and treatment adaptation.